The Effect of Hydrogel Containing Centella Asiatica Active Ingredient on Incision Wound Healing in Wistar Rats: A Systematic Review on VEGF and Fibroblasts - Arge Raviadi Muhammad; Renni Yuniati; B. Parish Budiono (Green Publisher Indonesia, 2026)
Centella asiatica, commonly known as pegagan or gotu kola, is a traditional medicinal plant widely used across Asia for its wound-healing properties. Its key active constituents—asiaticoside, madecassoside, asiatic acid, and madecassic acid—have been associated with enhanced collagen synthesis, modulation of inflammatory responses, and stimulation of angiogenesis. However, the specific biomolecular role of C. asiatica-based hydrogel formulations in incision wound healing, particularly through vascular endothelial growth factor (VEGF) expression and fibroblast proliferation in Wistar rats, has not been systematically synthesized. This systematic review aims to consolidate current evidence regarding the effects of C. asiatica hydrogel on VEGF expression and fibroblast activity in incision wound models in Wistar rats, and to elucidate the underlying biomolecular mechanisms. The findings indicate that C. asiatica hydrogel formulations significantly upregulate VEGF expression, enhance fibroblast density, accelerate wound closure, and promote collagen deposition compared to control groups. These effects are mediated through PI3K/AKT, TGF-β/Smad, and NF-κB signaling pathways. Hydrogel concentrations ranging from 0.5% to 10% w/w have demonstrated optimal biological activity. Overall, C. asiatica hydrogel presents a promising topical intervention for incision wound healing; however, standardized clinical trials are still required to confirm its therapeutic efficacy and optimal formulation parameters.